Modeling and Simulation of Fluid Catalytic Cracking Unit - Gupta, Raj Kumar Satyapal (My University, 2006)
Fluid catalytic cracking unit (FCCU) plays most important role in the economy of a modern refinery as it is used for value addition to the refinery products. Crude oil, as produced from the ground, contains hydrocarbons ranging from light gases and LPG to residues boiling above 343 0C (650 0F). Products of various boiling ranges can be obtained by distillation. Compared to the products demand, crude oil is short of lighter material in the boiling range of the transportation fuel (gasoline and diesel) and long on heavier material. Fluid catalytic cracking (FCC) units convert a portion of this heavy material into lighter products, chiefly gasoline and middle distillates. Because of the importance of FCCU in refining, considerable effort has been done on the modeling of this unit for better understanding and improved productivity. In last fifty years, the mathematical modeling of FCC unit have matured in many ways but the modeling continues to evolve to improve the closeness of models predictions with the real process whose hardware is ever-changing to meet the needs of petroleum refining. The FCC unit comprise of three stages: a riser reactor, a catalyst stripper, and a regenerator (along with other accessories). From modeling point of view, the riser reactor is of prime importance amongst these stages. Detailed modeling of the riser reactor is a challenging task for theoretical investigators not only due to complex hydrodynamics and the fact that there are thousands of unknown hydrocarbons in the FCC feed but also because of the involvement of different types of reactions taking place simultaneously. In the present work a new kinetic model of the riser reactor is developed using the common assumptions made by various researchers on various aspects of the riser modeling. The traditional and global approach of cracking kinetics is lumping. Mathematical models dealing with riser kinetics can be categorized into two main types. In one category the lumps are made on the basis of boiling range of feed stocks and corresponding products in the reaction system. This kind of model has an increasing trend in the number of lumps of the cracked gas components. The other approach is that in which the lumps are made on the basis of molecular structure characteristics of hydrocarbon group composition in reaction system. This category of models emphasizes on more detailed description of the feedstock. Theses models do not include chemical data such as type of reaction and reaction stoichiometry. The number of kinetic constants in these models increases very rapidly with the number of lumps. Moreover, the values of kinetic constants depend on the feedstock composition and must be determined for each combination of feedstock and catalyst. All these models assume that FCC feed and products are made of a certain number of lumps, and kinetic parameters for these lumps are estimated empirically considering the conversion of one lump to the other. In both of these categories, however, reaction kinetics being considered is that of conversion of one lump to another and not the cracking of an individual lump. More recently, models based upon single-events cracking, structure oriented lumping, and reactions in continuous mixture were proposed by various researchers. Nevertheless, the application of these models to catalytic cracking of industrial feedstocks (vacuum gas oil), is not realized because of the analytical complexities and computational limitations. In the present work, a new approach of kinetic scheme for the FCC riser is introduced which considers cracking of one lump (pseudocomponent) giving two other lumps in one single reaction step. The proposed model falls under the first category in which lumps are formed on the basis of boiling point, but in this approach, each individual lump is considered as a pure component with known physicochemical properties. Also, the reaction stoichiometry is considered. The proposed model also incorporates two phase flow and catalyst deactivation. Since a new cracking reaction mechanism is introduced, a new semi empirical approach based on normal probability distribution is also developed to estimate the cracking reactions rate constants. The pseudocomponents based approach for design and simulation of crude distillation unit is highly successful. To apply this approach to FCC simulation, it is assumed that one mole of a pseudocomponent on cracking gives one mole each of two other pseudocomponents and some amount of coke may also form. The feasibility of a cracking reaction is found by using the stoichiometry of that reaction. The reactions for which the molecular weight of a cracking pseudocomponent is equal to or more than the probable product pseudocomponents are considered feasible. In the present work, a new semi-empirical scheme for the estimation of rate constants is developed. This scheme makes the kinetic model more versatile. Six tunable parameters have been introduced to adjust more than ten thousand reaction rate constants needed to explain complete reaction mechanism in a typical FCC riser reactor. Riser reactor is conceptualized as having a number of small volume elements placed one over the other. The conditions at the inlet of the first volume element are known. The material and energy balance equations are solved in the volume elements considering the proposed reaction kinetics, two phase hydrodynamics, and catalyst deactivation. The various products yields, catalyst activity, and riser temperature are predicted all along the riser height. Plant data reported in the literature is used for the validation of the developed model. A sensitivity analysis of the proposed tuning parameters is done which suggested that the products yields were insensitive to one tuning parameter out of the proposed six tuning parameters. Also, the value obtained for one of the tuning parameter out of the proposed six tuning parameters was zero. These two tuning parameters were than dropped for the subsequent case studies for the simulation of the riser reactor and FCC unit. A regenerator model adopted from the literature is integrated with the proposed riser model to simulate the entire FCC unit. The steady state simulation of the FCC unit is then done to study the effect of various operating parameters on the performance of this unit. The work done in this study is organized into five chapters. The introduction of the fluid catalytic cracking (FCC) process/unit is presented in the first chapter, a literature review on the modeling and simulation of FCC unit follows in the second chapter. Chapter 3 deals with the riser model development. A regenerator model based on the model of Arbel et al. (1995) is also presented. In the last section the riser model and regenerator model are integrated to simulate the FCC unit. Results of the riser simulation, regenerator simulation, and entire FCC unit s simulation are presented and discussed in Chapter 4. The tuning parameters of the riser kinetic model are obtained using the plant data reported in literature. Then the sensitivity analysis is done by tracking the effect of change in products yields with the change in each tuning parameter s value (keeping other tuning parameters same). The less sensitive tuning parameters were dropped for subsequent simulations. Riser reactor model is validated by comparing with the plant data (reported in literature for different plants) and with an already existing riser reactor model s results. Regenerator simulation and comparison of regenerator model s results with the plant data are also presented in this chapter. The steady state simulation results of entire FCC unit along with the effect of changing C/O ratio and air flow to the regenerator on the process parameters is also included in this chapter. Chapter 5 summarizes the conclusions drawn from the study. Also, it is proposed that the proposed kinetic modeling approach for the riser kinetics may be used for the more advanced modeling of the FCC unit. Integration of this detailed kinetic scheme (any number of pseudocomponents) with the other aspects of riser modeling (hydrodynamics, heat and mass transfer, catalyst deactivation etc.) is easier as compared to other detailed kinetic models, as the resulting material and energy balance equations are easier to handle and solve.
In the present work, a new approach of kinetic scheme for the FCC riser is introduced which considers cracking of one lump (pseudo component) giving two other lumps in one single reaction step. The proposed model falls under the category of models in which lumps are formed on the basis of boiling point. In this approach, each individual lump is considered as a pure component with known physico-chemical properties. This scheme facilitates the consideration of cracking reactions’ stoichiometry. Since a new cracking reaction mechanism is introduced, a new semi empirical approach based on normal probability distribution is developed to estimate the cracking reactions’ rate constants. This approach makes the kinetic model more versatile. Six tunable parameters have been introduced to adjust more than ten thousand reaction rate constants needed to explain complete reaction mechanism in a typical FCC riser reactor. The model also incorporates two phase flow and catalyst deactivation. The various products’ yields, catalyst activity, and riser temperature are predicted all along the riser height. Plant data reported in the literature is used for the validation of the developed model. A sensitivity analysis of the proposed tuning parameters is done which suggested that the products’ yields were insensitive to one tuning parameter out of the proposed six tuning parameters. Also, the value obtained for one of the tuning parameter out of the proposed six tuning parameters was zero. These two tuning parameters were than dropped for the subsequent case studies for the simulation of the riser reactor and FCC unit. A regenerator model adopted from the literature is integrated with the proposed riser model to simulate the entire FCC unit. The steady state simulation of the FCC unit is then done to study the effect of operating parameters on the performance of this unit.
Keywords: Fluid Catalytic Cracking Modeling; FCC Modeling; Riser Kinetics; Modeling and Simulation; Pseudocomponents; Cracking Scheme